Antisense oligonucleotides targeting ORF1b block replication of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) - Dhorne-Pollet, Sophie; Fitzpatrick, Christopher; Da Costa, Bruno; Bourgon, Clara; Eléouët, Jean-François; Meunier, Nicolas; Burzio, Verónica A.; Delmas, Bernard; Barrey, Eric (Frontiers in Microbiology, 2022)
The ongoing COVID-19 pandemic continues to pose a need for new and efficient therapeutic strategies. We explored antisense therapy using oligonucleotides targeting the severe acute respiratory syndrome coronavirus (SARS-CoV-2) genome. We predicted in silico four antisense oligonucleotides (ASO gapmers with 100% PTO linkages and LNA modifications at their 5′ and 3′ends) targeting viral regions ORF1a, ORF1b, N and the 5′UTR of the SARS-CoV-2 genome. Efficiency of ASOs was tested by transfection in human ACE2-expressing HEK-293T cells and monkey VeroE6/TMPRSS2 cells infected with SARS-CoV-2. The ORF1b-targeting ASO was the most efficient, with a 71% reduction in the number of viral genome copies. N- and 5′UTR-targeting ASOs also significantly reduced viral replication by 55 and 63%, respectively, compared to non-related control ASO (ASO-C). Viral titration revealed a significant decrease in SARS-CoV-2 multiplication both in culture media and in cells. These results show that anti-ORF1b ASO can specifically reduce SARS-CoV-2 genome replication in vitro in two different cell infection models. The present study presents proof-of concept of antisense oligonucleotide technology as a promising therapeutic strategy for COVID-19.